2022
DOI: 10.1007/s00264-022-05611-x
|View full text |Cite
|
Sign up to set email alerts
|

Is intra-articular injection of autologous micro-fragmented adipose tissue effective in hip osteoarthritis? A three year follow-up

Abstract: Background Recently, increased attention on regenerative medicine and biological injective treatments have been proposed to restore native cartilage. Micro-fragmented adipose tissue (MFAT) has been studied for its anti-inflammatory, paracrine, and immunomodulatory effects. The long-term effects of MFAT are still poorly understood: the aim of the present study is to demonstrate how hip articular injections with autologous MFAT can have an impact on clinical outcomes. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For almost half a century, HA has been one of the most used injective drugs for the treatment of osteoarthritis considering both its physical-chemical properties and its interaction with cartilages' cells and extracellular matrixes (ECMs) [17]. In the last decades, the continuous search for the discovery of new and efective injective treatments has driven the interest in regenerative biologic therapies [18]. Autologous platelet-rich plasma (PRP) has been introduced as an alternative to HA for cases sufering from moderate knee osteoarthritis, leading to encouraging results in terms of both pain relief and functional recovery [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For almost half a century, HA has been one of the most used injective drugs for the treatment of osteoarthritis considering both its physical-chemical properties and its interaction with cartilages' cells and extracellular matrixes (ECMs) [17]. In the last decades, the continuous search for the discovery of new and efective injective treatments has driven the interest in regenerative biologic therapies [18]. Autologous platelet-rich plasma (PRP) has been introduced as an alternative to HA for cases sufering from moderate knee osteoarthritis, leading to encouraging results in terms of both pain relief and functional recovery [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…MFAT as a tissue graft can liberate MSCs for a considerable period of time and its injection application can reduce pain and may promote tissue regeneration and repair (Vezzani et al, 2018;Nava et al, 2019). Relevant studies have demonstrated that intraarticular injection of MFAT has yielded beneficial clinical results, but its use in discogenic pain is still in the preliminary stages of exploration (Ferracini et al, 2022;Natali et al, 2022). The ADSCs were not included in our study, which may be subject to cell source bias.…”
Section: Discussionmentioning
confidence: 99%
“…This follow‐up protocol was maintained until February 2023. Magnetic resonance examination performed 1 year postoperatively to confirm tendon healing condition, anterior drawer test, Lachman test, pivot shift test performed, IKDC score, 10 Knee Injury and Osteoarthritis Outcome Score (KOOS) score, 11 Lysholm score 12 used to evaluate affected side knee joint function, AOFAS score 13 used to evaluate donor area ankle joint function. The Opti Knee three‐dimensional motion measurement and analysis system‐Yidong Medical Infrared Motion Gait Analyzer (Shanghai Yidong Medical Technology Co. Shanghai, China) was used for bilateral knee joint and ankle joint analysis collection.…”
Section: Methodsmentioning
confidence: 99%